2012
DOI: 10.1038/nchembio.1153
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule activation of the TRAIL receptor DR5 in human cancer cells

Abstract: A poptosis in mammalian cells is executed by the proteolytic activities of caspases that are activated in response to apoptotic stimuli via two distinct signaling pathways 1 . These pathways have different initiator caspases that cleave and activate a common set of executioner caspases, including caspases 3, 6 and 7. The intrinsic (or mitochondrial) pathway of apoptosis is activated in response to DNA damage and other stress signals within the cell. Cytochrome c is consequently released from mitochondria into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 29 publications
2
81
0
1
Order By: Relevance
“…Death receptor-mediated (extrinsic) apoptosis represents one of the most important cytotoxic pathways activated by anticancer agents (11,27,(41)(42)(43)(44). In this study, we demonstrated, to our knowledge for the first time, that neddylation inhibition with MLN4924 induces DR5-mediated apoptosis in ESCC cells.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Death receptor-mediated (extrinsic) apoptosis represents one of the most important cytotoxic pathways activated by anticancer agents (11,27,(41)(42)(43)(44). In this study, we demonstrated, to our knowledge for the first time, that neddylation inhibition with MLN4924 induces DR5-mediated apoptosis in ESCC cells.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, we found that DR5-mediated apoptosis is ligand-independent since downregulation of its cognate ligand TRAIL failed to rescue DR5-induced apoptosis. Similarly, it is reported that unmitigated ER stress induced CHOP-mediated DR5 transcription and CASP8-mediated apoptosis in a TRAIL-independent manner (27,45). In addition, extrinsic apoptosis induced by MLN4924 in turn triggered intrinsic apoptosis through the CASP8/tBid axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Smac mimetic compound 3 and TRAIL were shown to synergistically induce caspase activation and apoptosis in glioblastoma cells (19). Recently, small molecules were identified that target TRAIL-R2 and interact with Smac mimetics to induce apoptosis in glioblastoma cells (20).…”
Section: Smac Mimetics In Combination With Trailmentioning
confidence: 99%
“…This process is achieved via the following two pathways: (1) exogenous pathway, where stimuli activate the death receptors Fas or CD95 on the cell surface; and (2) endogenous pathway, where increased permeability of the mitochondrial membrane and ER stress occurs [32]. In the mitochondrial pathway, the permeability of the mitochondrial membrane increases.…”
Section: Regulates Apoptosis In Host Cellsmentioning
confidence: 99%